Elaboração de um Atlas Virtual de Parasitologia e aplicação no Curso Técnico de Patologia Clínica - Silva, Wendel Tadeu da (2015)
Technology can assist in the development of learning, as revealed numerous features from the use of educational software. Objective: This project aims to develop educational software that facilitates basic education of Human Parasitology, aiming at a self-directed study and easily accessible to the student. Methodology: The photos for the drafting of the report were selected from the personal collection. The software was developed in Flash® and the chosen code editor was the Autorun®. The quality of the software was evaluated by 59 student volunteers of Clinical Pathology Technician Course belonging to Apollo College of Sorocaba - SP. All students to participate signed the Free Informed Consent and Enlightenment. Participants were subjected to a pre-test questionnaire (without the use of software), composed of 10 alternative questions about the essence of the parasitology study. Results: The students received hypermedia DVD, were instructed about the handling and access to software and after 30 days a questionnaire was administered post-test to all participants, made up of issues related to clinical parasitology issues included in the software. In addition to the application of pre and post-test questionnaires were asked students to answer qualitative questionnaire in relation to the handling and quality of software. The software is designed with 78 screens descriptive presentation of major pathogenic intestinal parasites laboratory routine. The parasites were distributed into groups of helminths and protozoa. The software was evaluated by the students of the Clinical Analysis Course (n = 59) of the College Apollo Sorocaba, where applied to a pre-test questionnaire (without software) on basic knowledge of parasitology area formed by 10 alternative questions. Soon after distributes the software and after 30 days if applied in the computer room of the College an advanced knowledge of post-test survey of the area, made up of 10 alternative tests. The test results showed improvement in students' knowledge, characterizing the importance of the use of software as a facilitator of didactic knowledge in the area. With analysis on the data collected, it appears that the software has achieved proposed learning objectives and interests presented by the students, to improve knowledge when using media. Discussion and Conclusion: Through the questionnaires it was found that knowledge of parasitology improved when compared to the pre-test and post-test. This software, according to the assessed, it is essential for learning Clinical Parasitologyducational implement